2002
DOI: 10.1111/1540-6210.00153
|View full text |Cite
|
Sign up to set email alerts
|

The Budget‐Minimizing Bureaucrat? Empirical Evidence from the Senior Executive Service

Abstract: In a representative democracy, we assume the populace exerts some control over the actions and outputs of government officials, ensuring they comport with public preferences. However, the growth of the fourth branch of government has created a paradox: Unelected bureaucrats now have the power to affect government decisions (Meier 1993; Rourke 1984; Aberbach, Putnam, and Rockman 1981). In this article, I rely on two competing theories of bureaucratic behavior‐representative‐bureaucracy theory and Niskanen's bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
1
33
0
1
Order By: Relevance
“…Here we distill only one critical point that can be used to develop a direct comparison between political and managerial-bureaucratic influences on performance. Research has demonstrated that on issues of concern to underrepresented racial and ethnic groups, a bureaucracy that is staffed by individuals drawn from such groups usually has values similar to those of the underrepresented groups (Dolan, 2000(Dolan, , 2002Hindera, 1993;Meier and Stewart, 1991). Bureaucrats who are representative in this way are more likely to advocate and work for the concerns of such groups.…”
Section: Representative Bureaucracymentioning
confidence: 99%
“…Here we distill only one critical point that can be used to develop a direct comparison between political and managerial-bureaucratic influences on performance. Research has demonstrated that on issues of concern to underrepresented racial and ethnic groups, a bureaucracy that is staffed by individuals drawn from such groups usually has values similar to those of the underrepresented groups (Dolan, 2000(Dolan, , 2002Hindera, 1993;Meier and Stewart, 1991). Bureaucrats who are representative in this way are more likely to advocate and work for the concerns of such groups.…”
Section: Representative Bureaucracymentioning
confidence: 99%
“…1997; Dolan 2000Dolan , 2002Selden and Selden 2001;Thielemann and Stewart 1996)? Second, how can passive representation contribute to active representation?…”
mentioning
confidence: 99%
“…Therefore, this observation is not a claim that agency managers are actually budget maximizers; on this, see Bowling, Cho, and Wright (2004) and Dolan (2002). Also, to emphasize this again, it does not necessarily mean that public managers cannot seek to achieve substantive normative goals.…”
Section: Notesmentioning
confidence: 99%